2008
DOI: 10.1159/000172965
|View full text |Cite
|
Sign up to set email alerts
|

Radical Resection of 202 Pediatric Craniopharyngiomas with Special Reference to the Surgical Approaches and Hypothalamic Protection

Abstract: Objective: The goal of this study was to disclose the appropriate surgical approaches to radically removing pediatric craniopharyngiomas with optimal hypothalamic protection. Methods: In 202 patients undergoing primary surgery from April 1997 to December 2002, eight approaches were used to remove craniopharyngiomas in the sellar region and the third ventricle. Among the eight approaches, the transcallosal-interseptal-interforniceal approach was used in 89 cases, the unilateral transfrontal interhemispheric app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
2
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 64 publications
(49 reference statements)
0
31
2
2
Order By: Relevance
“…Nevertheless, it has been shown that even after seemingly clean microscopic gross total resections (GTR), recurrence rates are as high as 18 to 60 % in pediatric series [6][7][8][9][10][11]. Another important factor reportedly predictive for tumor recurrence is tumor diameter greater than 4 to 5 cm [5].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has been shown that even after seemingly clean microscopic gross total resections (GTR), recurrence rates are as high as 18 to 60 % in pediatric series [6][7][8][9][10][11]. Another important factor reportedly predictive for tumor recurrence is tumor diameter greater than 4 to 5 cm [5].…”
Section: Introductionmentioning
confidence: 99%
“…In children, the most common operative approach is pterional. 14,27,35 Although this approach allows dissection of the sylvian fissure and access to the perisellar area, a significant amount of subfrontal retraction is often applied to allow successful resection. Removal of the orbital rim permits an increase in the angle of approach and the area of exposure without significant subfrontal retraction.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used approach, particularly in children, is the pterional approach, which allows subfrontal and transsylvian exposure of the suprasellar/parasellar area. 14,27,35 Other approaches include the transsphenoidal approach, the BIH approach, and the transcallosal interhemispheric approach. 35 Although each of these approaches can be used for successful craniopharyngioma resection, each also has limitations in terms of exposure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Diabetes insipidus (DI), especially if accompanied by impaired thirst sensation, can result in difficult to manage fluctuations in serum sodium levels. DI occurred in 81% of patients post-operatively in the series by Zhang et al [26] The Liverpool experience suggests that even a more conservative surgery will result in DI, but with preserved thirst mechanism which makes it much easier to manage the DI. [24] The intimate adherence of this tumor to the pituitary stalk and gland often leads to pan hypopituitarism following surgery.…”
Section: Complicationsmentioning
confidence: 96%